Cover Girls: South Asian American Women’s Vulnerability to Body Dissatisfaction, Arising from Cultural Differences and Western Appearance-Based Media - Khasru, Imaan (The Columbia Journal of Asia, 2022)
Existing studies show that exposure to appearance-based western media has a robust negative effect on women’s body esteem, eating practices, and self-image. This effect is mediated further by women’s individual characteristics, especially women’s pre-existing low body esteem, exposure to social comparison, and reliance on others’ approval for self-worth. A literature review reveals that (compared to white American women) South Asian American women have above-average exposure to objectification, social comparison, appearance-based commentary, and cultural conflict. Research suggests that all of these factors contribute to high body dissatisfaction and maladaptive eating in South Asian American women. Furthermore, American appearance-based media presents Asian women more infrequently and with more restrictions on physical features, compared to representation of white women. Therefore, appearance-based media may have a more salient (yet understudied) effect on the self-image and body esteem of South Asian American women than it does on white American women. This is but one example of a social phenomenon that has a more harmful effect on South Asian American women than their white American peers. The consequences of high vulnerability to body dissatisfaction include psychological distress and maladaptive eating.